The impact of the public procurement control system on the Hungarian public administration - Györgyi, Nyikos (Central European Public Administration Review, 2018)
The complexity of public procurement and the related controls are a significant issue that public authorities are facing in Hungary. The 'fear' of being controlled by state authorities and EU auditors is affecting decisions in public procurement. However, research on the effects of such a system is largely absent. The purpose of the article is to explore the functioning of the control system related to EU funded public procurements and to examine its actual and potential impact on the purchases of public authorities. The method is first an introduction of the features of the control system and then the analysis of data from the relevant bodies in order to see the effect of controls and possible difficulties with the system. The results show that despite the seemingly positive impact on the regularity of procedures, the interference in the decisions of public authorities and the delays caused are problematic. It is therefore suggested that the Hungarian government should consider streamlining the control process such as through checks based on samples or focusing on the most risky procedures. The research is the first academic analysis of data related to public procurement control in Hungary, yet it can already inspire the Hungarian and other governments to review the effectiveness of such procedures and to reduce administrative burdens for public authorities as much as possible.
Keywords: administrativna prepoved; javna naročila; javno naročanje; Madžarska; predhodni nadzor; revizija; skladi EU